Expatriate performance in international assignments: The role of cultural intelligence as dynamic intercultural competency - Che Rose, Raduan; Sri Ramalu, Subramaniam; Uli, Jegak; Kumar, Naresh (Canadian Center of Science and Education, 2010)
This paper investigates the affects of dynamic intercultural competency of cultural intelligence and its dimensions on expatriate job performance. Based on sample of 332 expatriates working in Malaysia, cultural intelligence found to be a vital intercultural competency that facilitates expatriates job performance in international assignments. Specifically, the results of this study reveal that expatriates in Malaysia with greater meta-cognitive and behavioral cultural intelligence fared better in their contextual performance. Greater assignment specific performance related to greater behavioral cultural intelligence. The findings of this study contributes to the body of knowledge in the cross-cultural management field as well as practical implication to expatriating firms especially in the area of selection and hiring of international candidates.